Mobilisasi Politik Muslimat Jawa Timur dalam Memenangkan Khofifah – Emil di Pemilihan Gubernur Jawa Timur 2018 - Chaniin Umamah (Universitas Airlangga, 2023)
This research discuss about how East Java’s Muslimat NU won the 2018 East Java Regional Election with candidates Khofifah Indar Parawansa and Emil Elistianto Dardak. Researcher studied aspects of political network and mobilization that Muslimat NU uses to win the election with candidates Khofifah Indar Parawansa and Emil Dardak. Research method used in this study was descriptive qualitative, gathering all data with these methods such as observation, deep interview, documentation, and secondary data. This research describes how the Muslimat NU utilizes their social resource with a very strong emotional bond, thus mobilizing their members to give support towards Khofifah-Emil in 2018 Regional Election. Taking advantage of their group activities, one for example is pengajian rutin. With the intention to socialize Khofifah-Emil’s candidacy, their vision, mission, and their work program as well.